A composite film with high barrier properties for high-purity polycrystalline silicon packaging and a preparation method thereof
By applying a protective film with a radical scavenger with sustained release function on the polyethylene film, the problem of aging of polyethylene film under ultraviolet light is solved, and the light resistance and barrier properties of the polyethylene film are significantly improved, and the light resistance and barrier properties of the polyethylene film are extended. Its service life is achieved.
Patent Information
- Application Number
- CN202411523355.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-30
AI Technical Summary
Polyethylene films produce free radicals under ultraviolet light, causing rapid aging, losing barrier properties and strength, and unable to effectively protect polysilicon.
A high-barrier, high-purity polycrystalline silicon packaging composite film is adopted. The composite film includes a polyvinyl film and a protective film. The protective film contains a free radical scavenger with sustained release function, and is modified by photosensitizer-phospholipase complex. Nanoliposomes encapsulate ascorbic acid glucoside, which releases sustainably to capture free radicals.
It significantly delays the aging process of polyethylene film and improves its light resistance, so that it will not experience significant aging in the condition of continuous exposure to the sun for at least 1 year, and maintains high barrier properties and strength.
Smart Images

Figure CN119019734B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of films, and relates to a composite film with high barrier properties for packaging high-purity polysilicon and a preparation method thereof. Background Art
[0002] Crystalline silicon is a form of elemental silicon. When molten elemental silicon solidifies under supercooling conditions, silicon atoms are arranged in the form of diamond lattices to form many crystal nuclei. If these crystal nuclei grow into grains with different crystal plane orientations, these grains combine to form polycrystalline silicon. It is a basic material widely used in the electronics industry to manufacture semiconductor radios, tape recorders, refrigerators, color TVs, VCRs, electronic computers, etc.
[0003] The commonly used packaging material in monocrystalline silicon packaging is polyethylene film. Polyethylene film has high barrier properties and plays a good moisture-proof and anti-oxidation role for polycrystalline silicon. However, polyethylene film has poor light resistance. The high energy of ultraviolet light can destroy the chemical bonds in the polyethylene molecular chain, causing the chain to break. After the chain breaks, fragments with unpaired electrons will be formed. These fragments are free radicals. In polyethylene, these free radicals will trigger a series of chain reactions. They will attack adjacent polyethylene molecular chains, causing more chain breaks and free radical generation. This reaction will be repeated continuously to form a free radical chain reaction, thereby accelerating the aging of polyethylene. Therefore, if the polyethylene film is not promptly eliminated of free radicals when exposed to ultraviolet light, the free radicals will produce a series of chain reactions, and the polyethylene film will quickly age. After aging, its barrier properties and strength will decrease. Not only will it not play a good moisture-proof and anti-oxidation role for polycrystalline silicon, but it will also be easily punctured by polycrystalline silicon. Summary of the invention
[0004] The purpose of the present invention is to provide a high-barrier composite film for high-purity polysilicon packaging and a preparation method thereof, which solves the problem that the polyethylene film generates free radicals under ultraviolet light and ages rapidly.
[0005] The technical solution adopted by the present invention is as follows:
[0006] A composite film for packaging high-purity polysilicon with high barrier properties, comprising a polyethylene base film and a protective film, wherein the protective film is adhered to the outer surface of the polyethylene base film;
[0007] The protective film includes a free radical scavenger with a sustained release function, and the free radical scavenger with a sustained release function includes the following components: ascorbyl glucoside, nanoliposomes, and a modifier;
[0008] The modifier is a photosensitizer-phospholipase complex, which includes phospholipase, a photosensitizer, and a coupling agent, wherein the mass ratio of the phospholipase to the photosensitizer is 1:3-4, and the mass ratio of the photosensitizer to the coupling agent is 1:1-2;
[0009] Nanoliposomes modified by photosensitizer-phospholipase complex encapsulate ascorbyl glucoside to form a free radical scavenger with sustained release function; wherein, the amount of ascorbyl glucoside added is 2.5%-2.6% of the mass of the nanoliposomes, and the amount of the photosensitizer-phospholipase complex added is 3.3% of the mass of the nanoliposomes.
[0010] At present, a single-component polyethylene film will show obvious aging such as cracking and breaking in about 6 months under continuous exposure conditions. This is because the generated free radicals are not blocked at the beginning, which triggers a series of reactions and causes chain breaks in the polyethylene film. The aging of the polyethylene film is a continuous process rather than a sudden process. The present invention delays the aging of the polyethylene film by eliminating the generated free radicals through a slow-release free radical scavenger when the polyethylene film is exposed to ultraviolet light, delaying a series of reactions caused by the free radicals, thereby delaying the aging of the polyethylene film. The polyethylene film coated with the protective film of the present invention, on the one hand, has a certain protective effect in itself and can enhance the light resistance of the polyethylene film. On the other hand, the present invention adds a free radical scavenger with a slow-release function to the protective film, which further enhances the light resistance of the polyethylene film. The polyethylene film coated with the protective film of the present invention will not show obvious aging such as cracking and breaking for one year under continuous exposure conditions.
[0011] The present invention uses nanoliposomes to encapsulate ascorbyl glucoside, which is a free radical scavenger. Ascorbyl glucoside can capture free radicals generated during the aging process of a polyethylene film and generate stable substances, thereby interrupting the free radical chain reaction and slowing down the aging process of the polyethylene film. Currently, when ascorbyl glucoside is used as a free radical scavenger, ascorbyl glucoside is directly added into the material to directly contact the external environment, and its stability will not be reduced due to environmental influences. In addition, a large amount of ascorbyl glucoside may be released at one time, resulting in the inability to maintain its free radical scavenging ability for a long time, thereby failing to significantly slow down the aging process of the polyethylene film. Therefore, the present invention uses nanoliposomes modified by photosensitizer-phospholipase complex as carriers to encapsulate ascorbyl glucoside, which, on the one hand, has a protective effect on ascorbyl glucoside, and on the other hand, by activating the activity of phospholipase under ultraviolet light, the phospholipase slowly enzymatically hydrolyzes the nanoliposomes, so that the nanoliposomes slowly disintegrate to release the ascorbyl glucoside inside, which has a slow release effect on the ascorbyl glucoside; the slow release of ascorbyl glucoside prolongs the free radical capture cycle of the ascorbyl glucoside, thereby significantly slowing down the aging process of the polyethylene film.
[0012] The amount of photosensitizer-phospholipase complex added will affect the light stability of nanoliposomes. If the amount of photosensitizer-phospholipase complex added is too much, the response ability to ultraviolet light is strong, the enzymatic hydrolysis efficiency of nanoliposomes is very high, resulting in too fast disintegration speed of nanoliposomes, and the slow release effect cannot be achieved; however, if the amount of photosensitizer-phospholipase complex added is too little, the enzymatic hydrolysis efficiency is too low, the speed of releasing ascorbyl glucoside is too slow, and the aging process of polyethylene film cannot be slowed down. Therefore, the present invention limits the amount of photosensitizer-phospholipase complex added.
[0013] The more ascorbyl glucoside is added, the higher the free radical elimination efficiency is, but too much ascorbyl glucoside will cause the tensile strength, elongation at break and mechanical strength of the protective film to decrease.
[0014] In the present invention, the mass ratio of phospholipase to photosensitizer is 1:3-4, and the amount of photosensitizer needs to be larger to enhance the responsiveness to ultraviolet light.
[0015] Furthermore, the free radical scavenger with sustained-release function is prepared by the following method:
[0016] A. Preparation of nanoliposomes: phospholipids, cholesterol and PEG-DSPE were dissolved in a mixed solution of methanol and chloroform at a mass ratio of 3:1:1, and the mixture was placed in a rotary evaporator and subjected to rotary evaporation at 60°C to remove the organic solvent and form a lipid film. The lipid film was then placed in a vacuum drying oven and vacuum dried at 50°C to obtain a dry liposome intermediate;
[0017] B. Encapsulation of ascorbyl glucoside: The dried liposome intermediate was added to a PBS buffer containing ascorbyl glucoside, dispersed using an ultrasonic disperser for 20 minutes, and then transferred to an oscillator and shaken at 55° C. for 1 hour to obtain a nanoliposome solution;
[0018] C. Modification of nanoliposomes: dissolving phospholipase A2 in PBS buffer to obtain a phospholipase solution; dissolving photosensitizer IR780 in DMSO to obtain a photosensitizer solution; then slowly dropping the photosensitizer solution into the phospholipase solution under stirring, adding a coupling agent maleimide-NHS ester, and reacting at 25° C. for 2-3 hours to obtain a photosensitizer-phospholipase complex; then slowly dropping the photosensitizer-phospholipase complex into the nanoliposome solution obtained in step B, stirring with a magnetic stirrer, stirring for 40 minutes, and reacting at room temperature for 8 hours. After the reaction, a modified nanoliposome solution is obtained, and finally the modified nanoliposome solution is centrifuged and low-temperature dried at -40° C. to obtain a free radical scavenger with a sustained release function.
[0019] The invention first adopts low-temperature drying, and utilizes the low-temperature environment to inhibit the activity of phospholipase, so as to prevent the phospholipase from enzymatically decomposing the nanoliposomes in the absence of light, thereby causing the ascorbyl glucoside in the nanoliposomes to be released in advance; the polyethylene film will age significantly only when it is irradiated with ultraviolet light of relatively high intensity; therefore, when it is exposed to ultraviolet light, the activity of the phospholipase in the invention will be activated under the action of a photosensitizer, and the high activity of the phospholipase can cause the nanoliposomes to disintegrate and release ascorbyl glucoside to capture free radicals generated by the aging of the polyethylene film under ultraviolet light, thereby delaying the aging of the polyethylene film.
[0020] The principle is: under ultraviolet light, the photosensitizer IR78 absorbs light energy and undergoes a photochemical reaction. The energy generated by the photochemical reaction is transferred to the phospholipase A2 molecule bound to the photosensitizer, causing the conformation of the phospholipase A2 molecule to change. The phospholipase A2 molecule after the conformational change has higher catalytic activity. The enhanced catalytic activity enables phospholipase A2 to more effectively hydrolyze the ester bonds in the phospholipid molecules, thereby forming a nanoliposome matrix, releasing ascorbic acid glucoside, and capturing free radicals, so that the polyethylene film can eliminate free radicals at the initial stage of generating free radicals under ultraviolet light, thereby avoiding a series of chain reactions caused by free radicals.
[0021] Furthermore, in the photosensitizer-phospholipase complex, the mass ratio of phospholipase A2 and photosensitizer IR78 is 1:3.5, and the mass ratio of photosensitizer IR78 and coupling agent maleimide-NHS ester is 1:2.
[0022] Furthermore, the protective film also includes 60 parts of polyvinyl alcohol, 30 parts of PAMAM dendritic polymer modified by methyl methacrylate, 15 parts of nano-alumina, 2 parts of mesoporous silica, and 10 parts of nano-titanium dioxide, and the amount of the free radical scavenger with sustained release function is 10% of the mass of the PAMAM dendritic polymer modified by methyl methacrylate;
[0023] The protective film is prepared by the following method: polyvinyl alcohol is dissolved in DMF and heated to be completely dissolved to obtain a polyvinyl alcohol solution for standby use; methyl methacrylate-modified PAMAM dendritic polymer, nano-alumina, mesoporous silica, PEG dispersant and nano-titanium dioxide are added to the DMF solution, and stirred at room temperature with a stirrer at a stirring speed of 500-1000 rpm for 30 minutes to obtain a mixed solution, and then the mixed solution and sodium dodecyl sulfate are added to the polyvinyl alcohol solution, and stirring is continued for 2-3 hours, and then a free radical scavenger with a sustained release function is added, and stirring is continued for 6-6.5 hours at room temperature to obtain a protective film solution, and finally the protective film solution is evenly coated on a polyethylene-based film, and dried at 70°C for 5 hours to obtain a protective film attached to the polyethylene-based film.
[0024] The invention uses polyvinyl alcohol as a main film-forming substance and uses a PAMAM dendritic polymer modified by methyl methacrylate as an auxiliary substance. Methyl methacrylate strengthens the film-forming property of the PAMAM dendritic polymer. The PAMAM dendritic polymer is composed of a central core, branch units and outer terminal groups, wherein the central core is usually composed of an amino group or a formamide group, the branch units are composed of an amine group or an amide group, and the outer terminal groups can be amine groups, carboxyl groups, etc. The structure of the PAMAM dendritic polymer presents a hierarchical branch structure, so that they have a higher molecular density and a higher number of surface groups. The structure of the PAMAM dendritic polymer enables the PAMAM dendritic polymer to have higher adhesion, high bonding strength with nano-alumina, mesoporous silica, nano-titanium dioxide and a free radical scavenger with a sustained release function, and the formed protective film has high stability.
[0025] Furthermore, the methyl methacrylate-modified PAMAM dendritic polymer is prepared by the following method: dissolving the PAMAM dendritic polymer in dimethyl sulfoxide to obtain a PAMAM dendritic polymer solution, then adding methyl methacrylate to the PAMAM dendritic polymer solution, uniformly mixing and heating to 65° C. under stirring conditions, adding ammonium persulfate initiator at 65° C., reacting for 2 hours under nitrogen protection, filtering and drying to obtain the methyl methacrylate-modified PAMAM dendritic polymer; wherein the amount of methyl methacrylate added is 10% of the mass of the PAMAM dendritic polymer.
[0026] Furthermore, the amount of PEG dispersant added is 2.5% of the total mass of the methyl methacrylate-modified PAMAM dendrimer, nano-alumina, mesoporous silica and nano-titanium dioxide, and the amount of sodium dodecyl sulfate added is 1% of the mass of polyvinyl alcohol.
[0027] Furthermore, the polyethylene-based film comprises low-density polyethylene, high-density polyethylene, and an antistatic agent, wherein the density of the low-density polyethylene is 0.91-0.93 g / cm 3 The density of the high-density polyethylene is 0.95-0.97 g / cm 3 The mass ratio of low-density polyethylene to high-density polyethylene is 3:2. Low-density polyethylene, high-density polyethylene and an antistatic agent are prepared by extrusion to obtain a polyethylene film, which is a polyethylene-based film.
[0028] Furthermore, the antistatic agent is an ethoxylated amine antistatic agent, and the amount of the ethoxylated amine antistatic agent added is 0.5% of the total mass of the low-density polyethylene and the high-density polyethylene.
[0029] A method for preparing a high-barrier composite film for high-purity polysilicon packaging, characterized in that it comprises the following steps:
[0030] S1, preparing a polyethylene-based film;
[0031] S2. Treating the outer surface of the polyethylene-based film: using 770 general treatment agent to treat the outer surface of the polyethylene-based film;
[0032] S3. Coating a protective film on the outer surface of the polyethylene film: dissolve polyvinyl alcohol in DMF and heat to completely dissolve to obtain a polyvinyl alcohol solution for use; add methyl methacrylate-modified PAMAM dendritic polymer, nano-alumina, mesoporous silica, PEG dispersant and nano-titanium dioxide to the DMF solution, and stir at room temperature with a stirrer at a stirring speed of 500-1000rpm for 30 minutes to obtain a mixed solution, then add the mixed solution and sodium dodecyl sulfate to the polyvinyl alcohol solution, continue stirring for 2-3 hours, then add a free radical scavenger with a sustained release function, and continue stirring at room temperature for 6-6.5 hours to obtain a protective film solution, finally evenly coat the protective film solution on the polyethylene film, and dry at 70°C for 5 hours to obtain a protective film attached to the polyethylene film, wherein the composite film of the protective film and the polyethylene film is a composite film with high barrier properties for high-purity polysilicon packaging.
[0033] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0034] 1. A composite film for packaging high-purity polycrystalline silicon with high barrier properties uses nanoliposomes modified with a photosensitizer-phospholipase complex as a carrier to encapsulate ascorbyl glucoside, which, on the one hand, protects the ascorbyl glucoside, and on the other hand, activates the activity of phospholipase under ultraviolet light, so that the phospholipase slowly enzymolyzes the nanoliposomes, causing the nanoliposomes to slowly disintegrate and release the ascorbyl glucoside inside, thereby slow-releasing the ascorbyl glucoside; the slow release of ascorbyl glucoside prolongs the free radical capture cycle of the ascorbyl glucoside, thereby significantly slowing down the aging process of the polyethylene film;
[0035] 2. The present invention first adopts low-temperature drying to utilize the low-temperature environment to inhibit the activity of phospholipase, thereby preventing phospholipase from enzymatically decomposing the nanoliposomes in the absence of light, thereby causing the ascorbyl glucoside in the nanoliposomes to be released prematurely. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative work, among which:
[0037] Figure 1 It is a SEM picture of the free radical scavenger with sustained release function of the present invention. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings herein can be arranged and designed in various different configurations.
[0039] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.
[0040] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0041] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0042] A composite film for packaging high-purity polysilicon with high barrier properties, comprising a polyethylene base film and a protective film, wherein the protective film is adhered to the outer surface of the polyethylene base film;
[0043] The protective film includes a free radical scavenger with a sustained release function, and the free radical scavenger with a sustained release function includes the following components: ascorbyl glucoside, nanoliposomes, and a modifier;
[0044] The modifier is a photosensitizer-phospholipase complex, which includes phospholipase, a photosensitizer, and a coupling agent, wherein the mass ratio of the phospholipase to the photosensitizer is 1:3-4, and the mass ratio of the photosensitizer to the coupling agent is 1:1-2;
[0045] Nanoliposomes modified by photosensitizer-phospholipase complex encapsulate ascorbyl glucoside to form a free radical scavenger with sustained release function; wherein, the amount of ascorbyl glucoside added is 2.5%-2.6% of the mass of the nanoliposomes, and the amount of the photosensitizer-phospholipase complex added is 3.3% of the mass of the nanoliposomes.
[0046] The present invention uses nanoliposomes to encapsulate ascorbyl glucoside, which is a free radical scavenger. Ascorbyl glucoside can capture free radicals generated during the aging process of a polyethylene film and generate stable substances, thereby interrupting the free radical chain reaction and slowing down the aging process of the polyethylene film. Currently, when ascorbyl glucoside is used as a free radical scavenger, ascorbyl glucoside is directly added into the material to directly contact the external environment, and its stability will not be reduced due to environmental influences. In addition, a large amount of ascorbyl glucoside may be released at one time, resulting in the inability to maintain its free radical scavenging ability for a long time, thereby failing to significantly slow down the aging process of the polyethylene film. Therefore, the present invention uses nanoliposomes modified by photosensitizer-phospholipase complex as carriers to encapsulate ascorbyl glucoside, which, on the one hand, has a protective effect on ascorbyl glucoside, and on the other hand, by activating the activity of phospholipase under ultraviolet light, the phospholipase slowly enzymatically hydrolyzes the nanoliposomes, so that the nanoliposomes slowly disintegrate to release the ascorbyl glucoside inside, which has a slow release effect on the ascorbyl glucoside; the slow release of ascorbyl glucoside prolongs the free radical capture cycle of the ascorbyl glucoside, thereby significantly slowing down the aging process of the polyethylene film.
[0047] The free radical scavenger with sustained-release function is prepared by the following method:
[0048] A. Preparation of nanoliposomes: phospholipids, cholesterol and PEG-DSPE were dissolved in a mixed solution of methanol and chloroform at a mass ratio of 3:1:1, and the mixture was placed in a rotary evaporator and subjected to rotary evaporation at 60°C to remove the organic solvent and form a lipid film. The lipid film was then placed in a vacuum drying oven and vacuum dried at 50°C to obtain a dry liposome intermediate;
[0049] B. Encapsulation of ascorbyl glucoside: The dried liposome intermediate was added to a PBS buffer containing ascorbyl glucoside, dispersed using an ultrasonic disperser for 20 minutes, and then transferred to an oscillator and shaken at 55° C. for 1 hour to obtain a nanoliposome solution;
[0050] C. Modification of nanoliposomes: dissolving phospholipase A2 in PBS buffer to obtain a phospholipase solution; dissolving photosensitizer IR780 in DMSO to obtain a photosensitizer solution; then slowly dropping the photosensitizer solution into the phospholipase solution under stirring, adding a coupling agent maleimide-NHS ester, and reacting at 25° C. for 2-3 hours to obtain a photosensitizer-phospholipase complex; then slowly dropping the photosensitizer-phospholipase complex into the nanoliposome solution obtained in step B, stirring with a magnetic stirrer, stirring for 30-40 minutes, and reacting at room temperature for 8-10 hours. After the reaction, a modified nanoliposome solution is obtained, and finally the modified nanoliposome solution is centrifuged and low-temperature dried at -40° C. to obtain a free radical scavenger with a sustained release function.
[0051] In the photosensitizer-phospholipase complex, the mass ratio of phospholipase A2 to photosensitizer IR78 is 1:3.5, and the mass ratio of photosensitizer IR78 to coupling agent maleimide-NHS ester is 1:2.
[0052] The protective film also includes 60 parts of polyvinyl alcohol, 30 parts of PAMAM dendritic polymer modified by methyl methacrylate, 15 parts of nano-alumina, 2 parts of mesoporous silica, and 10 parts of nano-titanium dioxide. The amount of the free radical scavenger with sustained release function is 10% of the mass of the PAMAM dendritic polymer modified by methyl methacrylate.
[0053] The protective film is prepared by the following method: polyvinyl alcohol is dissolved in DMF and heated to be completely dissolved to obtain a polyvinyl alcohol solution for standby use; methyl methacrylate-modified PAMAM dendritic polymer, nano-alumina, mesoporous silica, PEG dispersant and nano-titanium dioxide are added to the DMF solution, and stirred at room temperature with a stirrer at a stirring speed of 500-1000 rpm for 30 minutes to obtain a mixed solution, and then the mixed solution and sodium dodecyl sulfate are added to the polyvinyl alcohol solution, and stirring is continued for 2-3 hours, and then a free radical scavenger with a sustained release function is added, and stirring is continued for 6-6.5 hours at room temperature to obtain a protective film solution, and finally the protective film solution is evenly coated on a polyethylene-based film, and dried at 70°C for 5 hours to obtain a protective film attached to the polyethylene-based film.
[0054] The methyl methacrylate-modified PAMAM dendritic polymer is prepared by the following method: dissolving the PAMAM dendritic polymer in dimethyl sulfoxide to obtain a PAMAM dendritic polymer solution, then adding methyl methacrylate to the PAMAM dendritic polymer solution, uniformly mixing and heating to 65° C. under stirring conditions, adding ammonium persulfate initiator at 65° C., reacting for 2 hours under nitrogen protection to obtain the methyl methacrylate-modified PAMAM dendritic polymer; wherein the amount of methyl methacrylate added is 10% of the mass of the PAMAM dendritic polymer.
[0055] The PAMAM dendrimer is PAMAM G5-NH2 or PAMAM dendrimer with CAS No. 163442-68-0, ethylenediamine core, 5.0 generation.
[0056] The amount of PEG dispersant added is 2.5% of the total mass of the PAMAM dendrimer modified by methyl methacrylate, nano-alumina, mesoporous silica and nano-titanium dioxide, and the amount of sodium dodecyl sulfate added is 1% of the mass of polyvinyl alcohol.
[0057] The polyethylene-based film comprises low-density polyethylene, high-density polyethylene, and an antistatic agent, wherein the density of the low-density polyethylene is 0.91-0.93 g / cm 3 The density of the high-density polyethylene is 0.95-0.97 g / cm 3 The mass ratio of low-density polyethylene to high-density polyethylene is 3:2. Low-density polyethylene, high-density polyethylene and an antistatic agent are prepared by extrusion to obtain a polyethylene film, which is a polyethylene-based film.
[0058] The antistatic agent is an ethoxylated amine antistatic agent, and the amount of the ethoxylated amine antistatic agent added is 0.5% of the total mass of the low-density polyethylene and the high-density polyethylene.
[0059] A method for preparing a high-barrier composite film for high-purity polycrystalline silicon packaging, comprising the following steps:
[0060] S1, preparing a polyethylene-based film;
[0061] S2. Treating the outer surface of the polyethylene-based film: using 770 general treatment agent to treat the outer surface of the polyethylene-based film;
[0062] S3. Coating a protective film on the outer surface of the polyethylene film: dissolve polyvinyl alcohol in DMF and heat to completely dissolve to obtain a polyvinyl alcohol solution for use; add methyl methacrylate-modified PAMAM dendritic polymer, nano-alumina, mesoporous silica, PEG dispersant and nano-titanium dioxide to the DMF solution, and stir at room temperature with a stirrer at a stirring speed of 500-1000rpm for 30 minutes to obtain a mixed solution, then add the mixed solution and sodium dodecyl sulfate to the polyvinyl alcohol solution, continue stirring for 2-3 hours, then add a free radical scavenger with a sustained release function, and continue stirring at room temperature for 6-6.5 hours to obtain a protective film solution, finally evenly coat the protective film solution on the polyethylene film, and dry at 70°C for 5 hours to obtain a protective film attached to the polyethylene film, wherein the composite film of the protective film and the polyethylene film is a composite film with high barrier properties for high-purity polysilicon packaging. Example 1
[0063] A preferred embodiment of the present invention provides a high-barrier composite film for high-purity polysilicon packaging and a preparation method thereof.
[0064] A method for preparing a high-barrier composite film for high-purity polycrystalline silicon packaging, comprising the following steps:
[0065] S1. Prepare a polyethylene-based film, wherein the polyethylene-based film comprises low-density polyethylene, high-density polyethylene, and an antistatic agent, wherein the antistatic agent is an ethoxylated amine antistatic agent, and the amount of the ethoxylated amine antistatic agent added is 0.5% of the total mass of the low-density polyethylene and the high-density polyethylene, and the density of the low-density polyethylene is 0.91-0.93 g / cm 3 The density of the high-density polyethylene is 0.95-0.97 g / cm 3 , the mass ratio of low-density polyethylene to high-density polyethylene is 3:2, and the low-density polyethylene, high-density polyethylene, and antistatic agent are prepared by extrusion to obtain a polyethylene film;
[0066] S2. Treating the outer surface of the polyethylene-based film: using 770 general treatment agent to treat the outer surface of the polyethylene-based film;
[0067] S3, coating a protective film on the outer surface of the polyethylene film: the protective film comprises 60 parts of polyvinyl alcohol, 30 parts of PAMAM dendritic polymer modified by methyl methacrylate, 15 parts of nano-alumina, 2 parts of mesoporous silica, 10 parts of nano-titanium dioxide, and a free radical scavenger with a sustained release function, wherein the amount of the free radical scavenger with a sustained release function is 10% of the mass of the PAMAM dendritic polymer modified by methyl methacrylate; dissolving polyvinyl alcohol in DMF and heating to completely dissolve to obtain a polyvinyl alcohol solution for standby use; dissolving the PAMAM dendritic polymer modified by methyl methacrylate, nano-alumina, mesoporous silica, and nano-titanium dioxide; Silicon oxide, PEG dispersant and nano titanium dioxide are added to a DMF solution, and stirred at room temperature with a stirrer at a stirring speed of 1000 rpm for 30 minutes to obtain a mixed solution, and then the mixed solution and sodium dodecyl sulfate are added to a polyvinyl alcohol solution, and the stirring is continued for 3 hours, and then a free radical scavenger with a sustained release function is added, and the stirring is continued for 6 hours at room temperature to obtain a protective film solution, and finally the protective film solution is evenly coated on a polyethylene-based film, and dried at 70° C. for 5 hours to obtain a protective film attached to the polyethylene-based film, wherein the composite film of the protective film and the polyethylene-based film is a composite film for packaging high-purity polycrystalline silicon with high barrier properties;
[0068] The amount of PEG dispersant added is 2.5% of the total mass of PAMAM dendritic polymer modified by methyl methacrylate, nano-alumina, mesoporous silica and nano-titanium dioxide, and the amount of sodium dodecyl sulfate added is 1% of the mass of polyvinyl alcohol;
[0069] The preparation method of the methyl methacrylate-modified PAMAM dendritic polymer is as follows: dissolving the PAMAM dendritic polymer in dimethyl sulfoxide to obtain a PAMAM dendritic polymer solution, adding methyl methacrylate to the PAMAM dendritic polymer solution, uniformly mixing and heating to 65° C. under stirring conditions, adding the PAMAM dendritic polymer and an ammonium persulfate initiator of 1% of the total mass of methyl methacrylate at 65° C., reacting for 2 hours under nitrogen protection to obtain a methyl methacrylate-modified PAMAM dendritic polymer; wherein the amount of methyl methacrylate added is 10% of the mass of the PAMAM dendritic polymer, and the PAMAM dendritic polymer is PAMAM G5-NH2;
[0070] Wherein, the free radical scavenger with sustained-release function is prepared by the following method:
[0071] A. Preparation of nanoliposomes: phospholipids, cholesterol and PEG-DSPE were dissolved in a mixed solution of methanol and chloroform at a mass ratio of 3:1:1, and the mixture was placed in a rotary evaporator and subjected to rotary evaporation at 60°C to remove the organic solvent and form a lipid film. The lipid film was then placed in a vacuum drying oven and vacuum dried at 50°C to obtain a dry liposome intermediate;
[0072] B. Encapsulation of ascorbyl glucoside: The dried liposome intermediate was added to a PBS buffer containing ascorbyl glucoside, dispersed using an ultrasonic disperser for 20 minutes, and then transferred to an oscillator and shaken at 55° C. for 1 hour to obtain a nanoliposome solution;
[0073] C. Modification of nanoliposomes: dissolving phospholipase A2 in PBS buffer to obtain a phospholipase solution; dissolving photosensitizer IR780 in DMSO to obtain a photosensitizer solution; then slowly dropping the photosensitizer solution into the phospholipase solution under stirring, adding coupling agent maleimide-NHS ester, and reacting at 25°C for 3 hours to obtain a photosensitizer-phospholipase complex; then slowly dropping the photosensitizer-phospholipase complex into the nanoliposome solution obtained in step B, stirring with a magnetic stirrer, stirring for 40 minutes, and reacting at room temperature for 8 hours. After the reaction, a modified nanoliposome solution is obtained, and finally the modified nanoliposome solution is centrifuged and dried at -40°C to obtain a free radical scavenger with sustained release function, the microstructure of which is as follows: Figure 1 As shown; wherein the mass ratio of phospholipase A2 and photosensitizer IR78 is 1:3.5, the mass ratio of the photosensitizer IR78 and the coupling agent maleimide-NHS ester is 1:2, the amount of ascorbyl glucoside added is 2.5% of the mass of the nanoliposome, and the amount of the photosensitizer-phospholipase complex added is 3.3% of the mass of the nanoliposome.
[0074] In this embodiment, the thickness of the composite film used to package polycrystalline silicon is preferably 0.6 mm, the thickness of the polyethylene-based film is 0.4 mm, and the thickness of the protective film is 0.2 mm. Example 2
[0075] This example is based on Example 1, but different from Example 1 in that the amount of ascorbyl glucoside added is 2.6% of the mass of the nanoliposomes. Example 3
[0076] This embodiment is based on the embodiment 1, but is different from the embodiment 1 in that the mass ratio of phospholipase A2 to photosensitizer IR78 is 1:3. Example 4
[0077] This embodiment is based on the embodiment 1, but is different from the embodiment 1 in that the mass ratio of phospholipase A2 to photosensitizer IR78 is 1:4. Example 5
[0078] This embodiment is based on Embodiment 1, but is different from Embodiment 1 in that the mass ratio of photosensitizer IR78 to coupling agent maleimide-NHS ester is 1:1. Example 6
[0079] This embodiment is based on the embodiment 1, but is different from the embodiment 1 in that the PAMAM dendritic polymer is a PAMAM dendritic polymer with a CAS number of 163442-68-0, an ethylenediamine core, and a 5.0 generation. Comparative Example 1
[0080] This comparative example is based on Example 1, but differs from Example 1 in that the amount of ascorbyl glucoside added is 2.7% of the mass of the nanoliposomes. Comparative Example 2
[0081] This comparative example is based on Example 1, but differs from Example 1 in that the amount of ascorbyl glucoside added is 2.4% of the mass of the nanoliposomes. Comparative Example 3
[0082] This comparative example is based on Example 1, but different from Example 1 in that: this comparative example does not use nanoliposomes modified by photosensitizer-phospholipase complex to encapsulate ascorbyl glucoside, but directly adds an equal amount of ascorbyl glucoside as that in Example 1 into the protective film, and the protective film is prepared by the following method: polyvinyl alcohol is dissolved in DMF and heated to completely dissolve to obtain a polyvinyl alcohol solution for standby use; methyl methacrylate-modified PAMAM dendrimer, nano-alumina, mesoporous silica, PEG dispersant and nano-titanium dioxide are added into the DMF solution, and stirred at room temperature with a stirrer at a stirring speed of 500-1000 rpm for 30 minutes to obtain a mixed solution, and then the mixed solution and sodium dodecyl sulfate are added into the polyvinyl alcohol solution, and stirring is continued for 2-3 hours, and then ascorbyl glucoside is added, and stirring is continued for 6-6.5 hours at room temperature to obtain a protective film solution, and finally the protective film solution is evenly coated on a polyethylene-based film, and dried at 70°C for 5 hours to obtain a protective film attached to the polyethylene-based film. Comparative Example 4
[0083] This comparative example is based on Example 1, but is different from Example 1 in that this comparative example does not use a photosensitizer-phospholipase complex to modify the surface of the modified nanoliposomes, and the remaining steps are the same as those in Example 1. Comparative Example 5
[0084] This comparative example is based on Example 1, but is different from Example 1 in that: this comparative example does not use methyl methacrylate to modify the PAMAM dendritic polymer, but directly uses the PAMAM dendritic polymer to prepare the protective film.
[0085] Test Example 1
[0086] The water barrier properties, oxygen barrier properties and puncture resistance strength of the high-barrier composite film for high-purity polycrystalline silicon packaging prepared in Examples 1-6 and Comparative Examples 1-5 and the blank control group were tested. The blank control group was a polyethylene-based film without a protective film, and the preparation method of the polyethylene-based film was referenced to Example 1. The thickness of the polyethylene-based film of the high-barrier composite film for high-purity polycrystalline silicon packaging was 0.4 mm, and the thickness of the protective film was 0.2 mm; the thickness of the polyethylene-based film of the blank control group was 0.6 mm; the results are shown in Table 1.
[0087] Oxygen barrier performance testing method: The film oxygen barrier performance testing method directly adopts the existing technology, and uses the OX2 / 230 oxygen permeability test system to measure the oxygen permeability of the film. The unit is cm³ / m²·24h·0.1MPa. An oxygen permeability less than 2 indicates good barrier properties.
[0088] Water barrier performance testing method: Use a water vapor transmission rate tester to measure the water vapor barrier performance of the film. The testing method of the water vapor transmission rate tester is an existing technology and will not be explained in detail here. The smaller the water vapor transmission rate value, the better the barrier performance of the film; the water vapor transmission rate is 1g / m 2 .day.1atm or less indicates good water barrier properties;
[0089] The test method for puncture resistance strength is: test according to the national standard "Test method for puncture resistance of plastic films and sheets" (GB / T 37841-2019). This standard is applicable to soft plastic films with a thickness of less than 1mm, and the unit is N / mm.
[0090] Table 1 Test results of films after irradiation with 30W ultraviolet disinfection lamp
[0091] Oxygen Transmission Rate Water vapor transmission rate Puncture resistance Example 1 <1 <1 320 Example 2 <1 <1 321 Example 3 <1 <1 318 Example 4 <1 <1 306 Example 5 <1 <1 302 Example 6 <1 <1 322 Comparative Example 1 <1 <1 282 Comparative Example 2 <1 <1 300 Comparative Example 3 <1 <1 289 Comparative Example 4 <1 <1 301 Comparative Example 5 1.13 <1 185 Blank Group 1.2 1.16 120
[0092] As shown in Table 1, the puncture resistance of the composite film prepared by the present invention reaches more than 300N and the composite film prepared by the present invention has a barrier property better than that of the polyethylene-based film. The composite film prepared by the present invention has good oxygen and water barrier properties and can be used for packaging polysilicon.
[0093] Test Example 2
[0094] The high-barrier high-purity polycrystalline silicon packaging composite films prepared in Examples 1-6 and Comparative Examples 1-5 and the blank control group were subjected to an ultraviolet accelerated aging test. The test conditions were: the irradiance of the UVA-340 lamp at 340 nm was 1.35 W / m 2 , only UV light (100% UV light, no moisture, no dark cycle), the drying temperature is 50 ° C. Observe the aging of the film after 3 months, 6 months, 9 months, and 12 months of UV light.
[0095]
[0096] Combined with the data in Table 2, it can be seen that the light resistance of the present invention is good. The protective film in the present invention is equivalent to the coating of the polyethylene-based film. The polyethylene-based film with the protective film accelerated aging for more than 12 months will not show any aging; when the protective film does not add a free radical scavenger with a sustained release function, it can only rely on the light resistance of the protective film itself to delay the aging time of the polyethylene film, but the delay time is not long, and can only play a delaying effect of several months. Combined with Tables 1 and 2, it can be seen that the polyethylene-based composite film prepared by the present invention has high barrier properties and light resistance, and can preserve polysilicon for a long time.
[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions and improvements made by any technician familiar with the field within the spirit and principle of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high-barrier composite film for packaging high-purity polycrystalline silicon, characterized in that: It includes a polyethylene base film and a protective film, wherein the protective film is adhered to the outer surface of the polyethylene base film; The protective film includes a free radical scavenger with a sustained release function, and the free radical scavenger with a sustained release function includes the following components: ascorbyl glucoside, nanoliposomes, and a modifier; The modifier is a photosensitizer-phospholipase complex, which includes phospholipase, a photosensitizer, and a coupling agent, wherein the mass ratio of the phospholipase to the photosensitizer is 1:3-4, and the mass ratio of the photosensitizer to the coupling agent is 1:1-2; Nanoliposomes modified by photosensitizer-phospholipase complex encapsulate ascorbyl glucoside to form a free radical scavenger with sustained release function; wherein the amount of ascorbyl glucoside added is 2.5%-2.6% of the mass of the nanoliposomes, and the amount of the photosensitizer-phospholipase complex added is 3.3% of the mass of the nanoliposomes; The protective film also includes 60 parts of polyvinyl alcohol, 30 parts of PAMAM dendritic polymer modified by methyl methacrylate, 15 parts of nano-alumina, 2 parts of mesoporous silica, and 10 parts of nano-titanium dioxide. The amount of the free radical scavenger with sustained release function is 10% of the mass of the PAMAM dendritic polymer modified by methyl methacrylate. The protective film is prepared by the following method: dissolving polyvinyl alcohol in DMF and heating it to completely dissolve to obtain a polyvinyl alcohol solution for standby use; adding methyl methacrylate-modified PAMAM dendritic polymer, nano-alumina, mesoporous silica, PEG dispersant and nano-titanium dioxide to the DMF solution, stirring at room temperature with a stirrer at a stirring speed of 500-1000 rpm for 30 minutes to obtain a mixed solution, then adding the mixed solution and sodium dodecyl sulfate to the polyvinyl alcohol solution, continuing to stir for 2-3 hours, then adding a free radical scavenger with a sustained release function, continuing to stir at room temperature for 6-6.5 hours to obtain a protective film solution, and finally evenly coating the protective film solution on a polyethylene-based film, and drying at 70° C. for 5 hours to obtain a protective film attached to the polyethylene-based film; The methyl methacrylate-modified PAMAM dendritic polymer is prepared by the following method: dissolving the PAMAM dendritic polymer in dimethyl sulfoxide to obtain a PAMAM dendritic polymer solution, then adding methyl methacrylate to the PAMAM dendritic polymer solution, uniformly mixing and heating to 65° C. under stirring conditions, adding ammonium persulfate initiator at 65° C., reacting for 2 hours under nitrogen protection to obtain the methyl methacrylate-modified PAMAM dendritic polymer; wherein the amount of methyl methacrylate added is 10% of the mass of the PAMAM dendritic polymer.
2. The high-barrier composite film for packaging high-purity polycrystalline silicon according to claim 1, characterized in that: The free radical scavenger with sustained-release function is prepared by the following method: A. Preparation of nanoliposomes: phospholipids, cholesterol and PEG-DSPE were dissolved in a mixed solution of methanol and chloroform at a mass ratio of 3:1:1, and the mixture was placed in a rotary evaporator and subjected to rotary evaporation at 60°C to remove the organic solvent and form a lipid film. The lipid film was then placed in a vacuum drying oven and vacuum dried at 50°C to obtain a dry liposome intermediate; B. Encapsulation of ascorbyl glucoside: The dried liposome intermediate was added to a PBS buffer containing ascorbyl glucoside, dispersed using an ultrasonic disperser for 20 minutes, and then transferred to an oscillator and shaken at 55° C. for 1 hour to obtain a nanoliposome solution; C. Modification of nanoliposomes: dissolving phospholipase A2 in PBS buffer to obtain a phospholipase solution; and dissolving photosensitizer IR780 in DMSO to obtain a photosensitizer solution; Subsequently, under stirring conditions, the photosensitizer solution is slowly dropped into the phospholipase solution, and a coupling agent maleimide-NHS ester is added, and the reaction is carried out at 25° C. for 2-3 hours to obtain a photosensitizer-phospholipase complex; then the photosensitizer-phospholipase complex is slowly dropped into the nanoliposome solution obtained in step B, and a magnetic stirrer is used for stirring. After stirring for 40 minutes, the reaction is carried out at room temperature for 8 hours. After the reaction is completed, a modified nanoliposome solution is obtained. Finally, the modified nanoliposome solution is centrifuged and low-temperature dried at -40° C. to obtain a free radical scavenger with a sustained release function.
3. The high-barrier composite film for packaging high-purity polycrystalline silicon according to claim 2, characterized in that: In the photosensitizer-phospholipase complex, the mass ratio of phospholipase A2 to photosensitizer IR78 is 1:3.5, and the mass ratio of photosensitizer IR78 to coupling agent maleimide-NHS ester is 1:
2.
4. The high-barrier composite film for packaging high-purity polycrystalline silicon according to claim 1, characterized in that: The amount of PEG dispersant added is 2.5% of the total mass of the PAMAM dendrimer modified by methyl methacrylate, nano-alumina, mesoporous silica and nano-titanium dioxide, and the amount of sodium dodecyl sulfate added is 1% of the mass of polyvinyl alcohol.
5. The high-barrier composite film for packaging high-purity polycrystalline silicon according to claim 1, characterized in that: The polyethylene-based film comprises low-density polyethylene, high-density polyethylene, and an antistatic agent, wherein the density of the low-density polyethylene is 0.91-0.93 g / cm 3 The density of the high-density polyethylene is 0.95-0.97 g / cm 3 The mass ratio of low-density polyethylene to high-density polyethylene is 3:
2. Low-density polyethylene, high-density polyethylene and an antistatic agent are prepared by extrusion to obtain a polyethylene film, which is a polyethylene-based film.
6. The high-barrier composite film for packaging high-purity polycrystalline silicon according to claim 5, characterized in that: The antistatic agent is an ethoxylated amine antistatic agent, and the amount of the ethoxylated amine antistatic agent added is 0.5% of the total mass of the low-density polyethylene and the high-density polyethylene.
7. A method for preparing a high-barrier composite film for packaging high-purity polycrystalline silicon according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, preparing a polyethylene-based film; S2. Treating the outer surface of the polyethylene-based film: using 770 general treatment agent to treat the outer surface of the polyethylene-based film; S3. Coating a protective film on the outer surface of the polyethylene film: dissolve polyvinyl alcohol in DMF and heat to completely dissolve to obtain a polyvinyl alcohol solution for use; add methyl methacrylate-modified PAMAM dendritic polymer, nano-alumina, mesoporous silica, PEG dispersant and nano-titanium dioxide to the DMF solution, and stir at room temperature with a stirrer at a stirring speed of 500-1000rpm for 30 minutes to obtain a mixed solution, then add the mixed solution and sodium dodecyl sulfate to the polyvinyl alcohol solution, continue stirring for 2-3 hours, then add a free radical scavenger with a sustained release function, and continue stirring at room temperature for 6-6.5 hours to obtain a protective film solution, finally evenly coat the protective film solution on the polyethylene film, and dry at 70°C for 5 hours to obtain a protective film attached to the polyethylene film, wherein the composite film of the protective film and the polyethylene film is a composite film with high barrier properties for high-purity polysilicon packaging.
Citation Information
Patent Citations
PBAT composite film based on irradiation modification and preparation method thereof
CN105086383A
Preparation method of lipid temperature-sensitive gel dressing with whitening effect
CN116510068A